Analisis Yuridis Kewenangan Diskresi dan Pertanggung Jawaban Hukum dalam Pelaksanaan Tugas Dan Fungsi Kepolisian - Neovaldo Sitinjak (Syntax Idea, 2021)
Discretion is an authority given by law to law enforcement officials, especially the Police to act in special situations in accordance with the agency's own judgment and conscience. The problem raised is How the Implementation and Authority in Making Discretionary Decisions Against Minor Crimes in the Legal Area of the South Jayapura Sector Police, What is Legal Responsibility in Making Discretionary Decisions Against Minor Crimes in the Legal Area of the South Jayapura Sector Police. In the writing of this thesis, the author uses the juridical empirical research type, while the approach used is socio-legal research. Making the Discretionary decision that has been handled by the South Jayapura Sector Police in cases of minor theft crimes and also resolved by way of Restorative Justice, the South Jayapura Sector Police through Bhabinkamtibmas take discretionary decisions and conduct mediation by summoning both reporting and reported parties. As part of the state administration process, the Jayapura Selatan Sector Police are also bound by certain laws and procedures, and are controlled and accountable to the law. Likewise with the discretionary decision taken, the decision from the discretion itself really depends on the problems faced as well as the situation and conditions in the field experienced by the Jayapura Selatan Sector Police. Even though Police Discretion is situational and subjective, there is also a legal basis for discretion to be accounted for, so that it does not appear arbitrary.